Can Europe Prosper Without the Common Currency? A Historical Perspective - Notermans, Ton (Journal of Reviews on Global Economics, 2017)
The Eurocrisis displays an astonishing similarity to the causes of the Great Depression in the form of massive current account imbalances, destabilising capital flows, financial fragility, and the commitment to defending a fixed exchange rate arrangement by means of austerity and internal devaluation. From the interwar economic and political disaster Europe eventually drew the lesson that internal balance had to enjoy priority over external balance, giving rise to a three-decade long period of unprecedented economic growth after the Second World War. As Europe has again stumbled into many of the policy errors that caused the Great Depression, it will need to relearn some of these lessons. In particular, the paper suggests that Europeanisation has gone too far and that rather than completing the monetary Union, Europe’s prosperity and political stability would be better served by compartmentalisation of financial markets, vertical industrial policies and an escape clause in the common currency allowing for temporary exit in case of fundamental disequilibria.